Aktivitas Hepatoprotektor Temulawak pada Ayam yang Diinduksi Pemberian Parasetamol - Agung Adi Candra (Politeknik Negeri Lampung., 2013)
The purpose of this study was to determine the effect of Curcuma in affecting the liver based on the value of SGOT and SGPT. Twenty chickens that have been adapted for 2 weeks given paracetamol 1350 mg / kg bw for 7 daysThen examined SGOT and SGPT. After the animal was given treatment for 7 days 500mg/kgBB Curcuma. At the end of the maintenance performed tests SGOT and SGPT level.. paracetamol administration for 7 days at contributing to increased SGOT average of 129.6 to 160.6 as well as the average value of SGPT increased from 58.6 to 68 after 7 days of taking paracetamol. Giving curcuma after administration perasetamol for 7 days to reduce levels SGOT and SGPT chicken Keywords: Hepatoprotector, Curcuma, Paracetamol